Portable and low-cost solutions to the imaging of Paleolithic art objects: A comparison of photogrammetry and reflectance transformation imaging. (December 2016) - Porter, Samantha T.; Huber, Nadine; Hoyer, Christian; Floss, Harald
Abstract: Recent advances in technology have opened up a wide range of new documentary techniques to archaeologists and others working in the field of cultural heritage. Reflectance Transformation Imaging (RTI) and three-dimensional (3D) modeling using close-range photogrammetry are two photo-based methods that are becoming increasingly common. They have the benefits of being both relatively inexpensive and portable, meaning these methods can be applied under a wide variety of conditions by workers at nearly all levels of funding. This paper discusses the results that were achieved by applying these techniques to a mobiliary art object from the Paleolithic site of Solutré (Burgundy, France) featuring fine engravings. We were able to successfully enhance the visibility of modifications made to the case study object using both RTI and close range photogrammetry. We conclude that these methods can be seen as complimentary, and that the resulting products may be used for several purposes including the creation of relevés, stylistic analysis, and the dissemination of digital object representations for both scholarly publication and public engagement. Graphical abstract: Highlights: We used reflectance transformation imaging and photogrammetry on the same object. We were able to produce enhanced and high resolution imagery, and 3D models. Low cost methods are a useful tool for the study of mobiliary art objects.